2016
DOI: 10.13005/bbra/2000
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Borage on hipocampal TNF-α protein and gene in the Amyloid β-Peptide(25–35)-Induced of Alzheimer model in rat

Abstract: Alzheimer's disease (AD) is a neurodegenerative disorder and most common form of dementia that leads to memory impairment. In the present study we have examined the investigating effect of Borago officinale on hipocampal TNF-α α α α α protein in the Beta Amyloid peptid induced of inflammation in the rat. Wistar male rats received intrahippocampal (IHP) injection of the Aβ β β β β(25-35) and borage extract orally (100 mg/ kg).inflamation was confirmed by pathologist.in order to measure the expression of the TNF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…These impairments are caused by mainly loss of cholinergic neurons especially in basal forebrain cholinergic neurons (BFCN) as a result of extracellular deposition of Aβ proteins (Senile Plaques) and intracellular formation of neuro brillary tangles (NFTs) in the brain speci cally in the hippocampus region [2,3]. It is reported that these lesions (i. e. Aβ deposition and NFTs formation) can be resulted from decreasing in neurotrophic factors mainly brain-derived neurotrophic factor (BDNF) and nerve growth factor (NGF) [4] which is nally led to apoptosis and cell death [5]. Hence, apoptosis, also known as programmed cell death, contributes to neuronal cell death in AD as a result of trophic factor deprivation [6].…”
Section: Introductionmentioning
confidence: 99%
“…These impairments are caused by mainly loss of cholinergic neurons especially in basal forebrain cholinergic neurons (BFCN) as a result of extracellular deposition of Aβ proteins (Senile Plaques) and intracellular formation of neuro brillary tangles (NFTs) in the brain speci cally in the hippocampus region [2,3]. It is reported that these lesions (i. e. Aβ deposition and NFTs formation) can be resulted from decreasing in neurotrophic factors mainly brain-derived neurotrophic factor (BDNF) and nerve growth factor (NGF) [4] which is nally led to apoptosis and cell death [5]. Hence, apoptosis, also known as programmed cell death, contributes to neuronal cell death in AD as a result of trophic factor deprivation [6].…”
Section: Introductionmentioning
confidence: 99%
“…These impairments are mainly caused by the loss of cholinergic neurons, especially in basal forebrain cholinergic neurons (BFCN), as a result of extracellular deposition of Aβ proteins (senile plaques) and intracellular formation of neuro brillary tangles (NFTs) in the brain, especially in the hippocampus [2,3]. It has been reported that these lesions (i.e., Aβ deposition and NFT formation) can result from a decrease in neurotrophic factors, mainly the brain-derived neurotrophic factor (BDNF) and nerve growth factor (NGF) [4], and nally lead to apoptosis and cell death [5]. Therefore, apoptosis, also known as programmed cell death, contributes to neuronal cell death in AD due to trophic factor deprivation [6].…”
Section: Introductionmentioning
confidence: 99%